Dynamic Coupling Analysis of a Spatial 6-DOF Electro-Hydraulic Parallel Manipulator Using a Modal Decoupling Method. (6th February 2013) - Yang, Chifu; Han, Junwei
The workspace of a spatial 6-DOF electro-hydraulic parallel manipulator is strongly coupled, due to its multi-closed-loop kinematic structure and the coupling complicates motion planning and control of the parallel manipulator. This paper clearly analyses the strong dynamic coupling property in the workspace of a spatial 6-DOF parallel manipulator, using modal decoupling theory and a frequency responses characteristics analysis method. The dynamic model of a spatial 6-DOF electro-hydraulic parallel manipulator is expressed with the Kane method and hydromechanics principles. The modal analysis method is used to establish the map between strong coupling workspace and decoupled modal space and the dynamic coupling relationship and coupling strength between workspaces are exactly revealed. The quantitative evaluation index of dynamic coupling is presented. Moreover, the relationship between dynamic coupling effects and input is discussed through applying frequency characteristics analysis. Experimental results show the workspace of the parallel manipulator is strongly coupled and the coupling property is coincident with theoretical results.